EFFECT OF ESSENTIAL OILS ON THE MYCELIAL GROWTH OF ð˜—ð˜ºð˜µð˜©ð˜ªð˜¶ð˜® sp. CAUSAL AGENT OF DAMPING OFF IN LETTUCE - Paiva, Gabriel Ferreira; Malanski Barbieri, Tayane PatrÃcia de Oliveira; Melo, Bruna da Silva; GonÃ§alves, Francisco JosÃ© Teixeira; DonegÃ¡, Mateus Augusto (REVISTA DE AGRICULTURA, 2021)
This work aims to test the antifungal effect of essential oils of Eucalyptus citriodora, Mentha spicata and Mentha arvensis in vitro. The study was carried out in a completely randomized block design, with a factorial scheme of three treatments and five concentrations, in concentrations of 0, 50, 100, 500 and 1000 mg ml -1 . The data obtained were subjected to analysis of variance and compared using the 5% t test. It was possible to conclude that the tested oils have compounds effective in inhibiting the mycelial growth of Pythium sp., suggesting the possibility of use for the formulation of biofumigants for soil treatment.